Quantitative Magnetic Resonance Imaging of Enzyme Activity on the Cell Surface: In Vitro and In Vivo Monitoring of ADP-Ribosyltransferase 2 on T Cells - Peter Bannas; Oliver Graumann; Philipp Balcerak; Kersten Peldschus; Michael Gerhard Kaul; Heinrich Hohenberg; Friedrich Haag; Gerhard Adam; Harald Ittrich; Friedrich Koch-Nolte (Molecular Imaging)
The objective of this study was to quantify enzymatic activity on the surface of T cells by magnetic resonance imaging (MRI) using R2 and R2* relaxometry. Lymphoma cells expressing adenosine diphosphate (ADP)-ribosyltransferase 2 (ART2) were incubated with increasing doses of its substrate etheno–nicotinamide adenine dinucleotide (NAD), resulting in increasing amounts of surface protein ADP-ribosylation. Etheno-ADP-ribosylated proteins were detected with monoclonal antibody 1G4 and superparamagnetic iron oxide conjugated secondary antibodies (Ab-SPIO). Labeling efficiency was determined with R2 and R2* relaxometry on a clinical 3.0 T scanner. Parallel aliquots of cells were analyzed by flow cytometry. Cell-bound SPIO conjugates were detected by immunofluorescence and electron microscopy and quantified by atomic absorption spectroscopy. To mimic an inflammatory site in vivo, Ab-SPIO-labeled cells were injected subcutaneously in mice and analyzed by MRI. Immunofluorescence and electron microscopy confirmed cell-surface localization of Ab-SPIO. MRI of Ab-SPIO-labeled cells showed a corresponding signal reduction. Increases in R2 and R2* determined by magnetic resonance relaxometry correlated linearly with the expression level of ART2 and the concentration of the ART2 substrate etheno-NAD. R2 and R2* increases correlated linearly with the results from flow cytometry and atomic absorption spectroscopy analyses. Quantitative R2 and R2* mapping enable noninvasive determination of enzymatic activity on T cells and holds promise for characterization of inflammatory sites in vivo by MRI.